Suppression of Plasmodium chabaudi Parasitemia Is Independent of the Action of Reactive Oxygen Intermediates and/or Nitric Oxide - Gillman, Brad M. (American Society for Microbiology, 2004)
The killing of blood-stage malaria parasites in vivo has been attributed to reactive intermediates of oxygen (ROI) and of nitrogen (RNI). However, in the case of the latter, this contention is challenged by recent observations that parasitemia was not exacerbated in nitric oxide synthase (NOS) knockout (KO) (NOS2(−/−) or NOS3(−/−)) mice or in mice treated with NOS inhibitors. We now report that the time course shows that Plasmodium chabaudi parasitemia in NADPH oxidase KO (p47(phox−/−)) mice also was not exacerbated, suggesting a minimal role for ROI-mediated killing of blood-stage parasites. It is possible that the production of protective antibodies during malaria may mask the function of ROI and/or RNI. However, parasitemia in B-cell-deficient J(H)(−/−) × NOS2(−/−) or J(H)(−/−) × p47(phox−/−) mice was not exacerbated. In contrast, the magnitude of peak parasitemia was significantly enhanced in p47(phox−/−) mice treated with the xanthine oxidase inhibitor allopurinol, but the duration of patent parasitemia was not prolonged. Whereas the time course of parasitemia in NOS2(−/−) × p47(phox−/−) mice was nearly identical to that seen in normal control mice, allopurinol treatment of these double-KO mice also enhanced the magnitude of peak parasitemia. Thus, ROI generated via the xanthine oxidase pathway contribute to the control of ascending P. chabaudi parasitemia during acute malaria but alone are insufficient to suppress parasitemia to subpatent levels. Together, these results indicate that ROI or RNI can contribute to, but are not essential for, the suppression of parasitemia during blood-stage malaria.